Vertebral Artery Stenosis Caused by Cervical Osteophyte: A Rare and Reversible Cause of Vertebrobasilar Insufficiency. Case Report - Cembraneli, Pedro Nogarotto; Faria Cavalcante, Julia Brasileiro de; Faria Cavalcante, Renata Brasileiro de; Cembraneli, Italo Nogarotto; Lopes, Leonardo Taveira; Silva Cavalcante, Jose Edison da; Cardoso, Alessandro Fonseca; Cardoso, Chrystiano Fonseca; Zanini, Marco Antonio [UNESP] (Georg Thieme Verlag Kg, 2024)
Bow Hunter syndrome manifests when the vertebral artery is compressed following head rotation. Symptomatic compression with vertebral artery stenosis due to cervical osteophytes is a rare cause and occurs due to a progressive degenerative process. In most cases, compression originates anteromedially from the uncinate process and is asymptomatic due to the competence of the contralateral vertebral artery. In the described patient, compression presented superomedially due to osteophytes in the superior articular facet of the C5 vertebra, and the contralateral vertebral artery was obstructed. Careful evaluation with imaging, mainly preoperative 3D angiotomography, is necessary to determine the most beneficial approach for decompression. The treatment of choice for symptomatic compression induced by cervical spondylosis is decompression surgery.
Keywords: vertebral artery; vertebrobasilar insufficiency; osteophyte; Bow Hunter's Syndrome; art & eacute;ria vertebral; insufici & ecirc;ncia vertebrobasilar; oste & oacute;fito; S & iacute;ndrome de Bow Hunter